Energy expenditure and dietary intake of athletes during an ultraendurance event developed by hiking, cycling and mountain climbing - Rejc, E.; Lazzer, S.; Antonutto, G. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: To investigate exercise intensity, energy expenditure and energy balance of athletes during an ultraendurance event (UE) consisting in hiking, cycling and mountain climbing. METHODS: Four athletes participated in this study. Maximal oxygen uptake (V.O2max) and "V.O2-heart rate" relationships during cycling and walking were determined by indirect calorimetry during two graded exercise tests. Body mass and body fat mass were measured before and after the UE. During the UE, heart rate (HR), diet intake, gastrointestinal disturbances and route characteristics were monitored. RESULTS: UE duration was 19 h29 min over a distance of 108 km, with 6768 meters of altitude difference. Body mass and percent of body fat mass tended to decrease after UE (-3.2% and -8.9%, respectively). During the locomotion phases, mean exercise intensity was 50.8±10.4% of V.O2max and 65.8±7.6% of HRmax. Energy expenditure amounted to 51.0±3.4 MJ. Energy supplied from diet and body fat mass oxidation was 20.4±10.7 MJ and 17.3±2.4 MJ, respectively. During the UE, athletes did not suffer of any gastrointestinal disorder. CONCLUSION: Mean exercise intensity corresponded to 51% V.O2max: it was independent from the locomotion type, and it can be considered an adequate intensity for UEs with similar characteristics. Although athletes successfully completed the UE, the self regulation of energy intake led athletes to a negative energy balance. Estimation of energy expenditure prior the begin of UEs would allow athletes to better plan the diet energy intake.